WELLBEING AND WELLNESS: THE MAIN NEEDS FOR USERS OF INTERIOR DESIGN SERVICES - Putri Refinda Yuan Ochtisha; Kusumowidagdo, Astrid (Universitas Ciputra Surabaya, 2024)
The interior design business is growing along with customers' increasing interest in ease of service. Increased competition drives the need for differentiation by integrating well-being and wellness into building design through the Wellness-Centric Approach. This research aims to identify customer needs and preferences related to interest in well-being and wellness in building design. Involving observations from consultants, literature reviews, and surveys, the findings present an analysis of the industry, market forces, and key trends. Awareness of well-being and wellness in building design is increasing, although it is not yet aligned with the psychological aspects. Competition, consumer preferences, technology, and regulations affect service quality and pricing. The lack of wellness-focused consultants and technological knowledge, as well as government regulations, also play an important role. Key trends in wellness design include air quality, technology, color, eco-friendly materials, natural elements, and health representation, opening up competitive opportunities for well-being and wellness design. Opportunities arise from increased real estate investment and shifting consumer preferences due to the COVID-19 pandemic. Innovation in line with key trends and consumer awareness opens up opportunities for building design focused on health and well-being. The results show that well-being and wellness-oriented interior design provides a competitive advantage in the consulting business. Keywords: Interior Architecture, Competitive Advantage, Wellbeing, Wellness.